2016
DOI: 10.1136/heartjnl-2015-308616
|View full text |Cite
|
Sign up to set email alerts
|

Patient and hospital determinants of primary percutaneous coronary intervention in England, 2003–2013

Abstract: ObjectivePrimary percutaneous coronary intervention (PPCI) for ST-elevation myocardial infarction (STEMI) is insufficiently implemented in many countries. We investigated patient and hospital characteristics associated with PPCI utilisation.MethodsWhole country registry data (MINAP, Myocardial Ischaemia National Audit Project) comprising PPCI-capable National Health Service trusts in England (84 hospital trusts; 92 350 hospitalisations; 90 489 patients), 2003–2013. Multilevel Poisson regression modelled the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…[21][22][23][24] For patients with NSTEMI, temporal improvements in survival were explained by an increase in the uptake of an invasive coronary strategy, 15 and for STEMI associated with the use of evidence-based pharmacotherapies and primary PCI. 25 The implementation of a national primary PCI programme has enabled 24/7 availability of guideline-recommended treatments in the UK, 15,26 although there remains variation across Europe. 27,28 Over the study period we found a decrease in absolute mortality, also noted by others, 23,29,30 but also a reduction in the variation in mortality associated with time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] For patients with NSTEMI, temporal improvements in survival were explained by an increase in the uptake of an invasive coronary strategy, 15 and for STEMI associated with the use of evidence-based pharmacotherapies and primary PCI. 25 The implementation of a national primary PCI programme has enabled 24/7 availability of guideline-recommended treatments in the UK, 15,26 although there remains variation across Europe. 27,28 Over the study period we found a decrease in absolute mortality, also noted by others, 23,29,30 but also a reduction in the variation in mortality associated with time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…Terkelsen and colleagues demonstrated a more than 1 h reduction of system delay among patients diagnosed in the prehospital setting and triaged directly to PPCI, compared to patients without prehospital ECG recording and admission to a local hospital [16]. Prehospital ECG diagnosis has been successfully implemented worldwide and field triage directly to PPCI is associated with improved outcome, Figure 2 [17][18][19][20][21]. Danish nationwide data suggests that each additional hour spent is associated with a 10% relative increase in both mortality and the risk of heart failure [18,22], and that shorter system delays are associated with an increased proportion of patients returning to the labor market, Figure 3 [23].…”
Section: Prehospital Ecg Diagnosis Of Patients With St Elevation Myocmentioning
confidence: 99%
“…, Hall et al . ); cardiovascular rehabilitation (Beswick et al . , Harrison & Wardle ); and stroke care (Rudd et al .…”
Section: Resultsmentioning
confidence: 99%